Current State of the Worldwide Renewable Energy Generation (2021)
The purpose of this study is to undertake a global review of the renewable energy generation's current state, specifically in the area of photovoltaic (PV) solar energy, wind energy, bioenergy, and hybrid power systems for electricity production. This article presents the most relevant aspects of the progress and the experiences of countries aiming at the construction and implementation of these technologies. It also quotes studies that include the advances of countries seeking to contribute to the decrease of greenhouse gas emission or that due to their geographic and environmental conditions are attempting to improve the access and the quality of the electric energy generation, involving especially remote communities that could hardly connect to the national power grid because of techno-economic reasons. These renewable energy studies could lead off to evaluate the impact of clean energy on the global energy supply and demand. Although in general, these technologies require high investments hardly competitive with traditional energy, with the support of stable policies and government subsidies, these become a choice that grows exponentially every day concerning efficiency and the reduction of costs, which can build trust in new investors.